16th International IEEE Conference on Intelligent Transportation Systems (ITSC 2013) 2013
DOI: 10.1109/itsc.2013.6728217
|View full text |Cite
|
Sign up to set email alerts
|

Road occupancy prediction of traffic participants

Abstract: We predict the road occupancy of traffic participants for collision avoidance systems. The occupancy sets are computed for consecutive time intervals and contain all reachable positions of traffic participants in compliance with a proposed dynamic model. Those sets make it possible to check if planned emergency maneuvers are collision-free in all possible future scenarios. However, no algorithm exists for exactly computing the occupancy when the model forbids unrealistic behavior such as leaving road boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…This paper is an extension to the authors' previous work [3], [51], where it was shown that the occupancy prediction of other traffic participants can be computed in a formal manner. This work significantly extends previous work:…”
Section: Introductionmentioning
confidence: 89%
“…This paper is an extension to the authors' previous work [3], [51], where it was shown that the occupancy prediction of other traffic participants can be computed in a formal manner. This work significantly extends previous work:…”
Section: Introductionmentioning
confidence: 89%
“…We overapproximate the set of solutions Z(t) to facilitate its computation. If we obtain a new model M with constraints C ⊆ C and set Z (t) by relaxing the constraints on model M or by removing constraints C i (z, u) from C, then Z(t) ⊆ Z (t) holds [20]. The overapproximation implies that Z (t) = ∅ ⇒ Z(t) = ∅ holds; therefore, maneuver templates can be discarded despite the overapproximation of Z(t).…”
Section: Problem Statement and Methodologymentioning
confidence: 99%
“…To guarantee safety, all possible trajectories of the leading vehicle must be considered. To this end, an overapproximative occupancy set which encloses all possible occupancies is computed [28] for a given time horizon T h2 .…”
Section: Fail-safe Motion Plannermentioning
confidence: 99%
“…In [28], a method for computing an overapproximative set which encloses all possible trajectories of the leading vehicle is proposed for a given time horizon T h 2 . To this end, two abstracted models for the leading vehicles are presented: They consider constraints derived from the traffic rules listed in the Vienna Convention on Road Traffic [31] and physical constraints.…”
Section: ➁ Emergency Trajectorymentioning
confidence: 99%
See 1 more Smart Citation